The Influence of Attitudes Toward Risk on the Value of Forecasting - Blair, Roger D.; Romano, Richard E. (Quarterly Journal of Economics, 1988)
Journal Article The Influence of Attitudes Toward Risk on the Value of Forecasting Get access Roger D. Blair, Roger D. Blair Department of Economics, University of Florida Search for other works by this author on: Oxford Academic Google Scholar Richard E. Romano Richard E. Romano Department of Economics, University of Florida Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 103, Issue 2, May 1988, Pages 387–396, https://doi.org/10.2307/1885119 Published: 01 May 1988